POLA PERGERAKAN WISATAWAN BUNTU BURAKE DI KABUPATEN TANA TORAJA, SULAWESI SELATAN - Sri Mariati; Kaleb Yusuf Sinay; Himawan Brahmantyo; Myrza Rahmanita; Fahrul Husein Habibie (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
The main point of interest in Buntu Burake tourist destination is a statue of Jesus Christ with height of 45 meters that resembles the Christ the Redeemer Statue in Rio de Janeiro, Brazil. This study aims to analyze the mechanism of the movement of tourists to the tourist destination of Buntu Burake. The authors use descriptive qualitative methods, with observation, in-depth interviews with key informants and tourists as a method of data collection, and in-depth discussion using a semi-structured interview guide. The results of this study indicate that the movement mechanism of tourists is the neighbourhood omplex as much as 35% and base site as much as 26%, and the remaining 13% stopover, chaining loop 13%, destination region loop 9%, and single point 4%. The right pattern of tourist movement to be applied in Buntu Burake is a chaining loop and a destination region loop, because they can direct tourists through a more orderly flow of movement.